2007
DOI: 10.1159/000108635
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine Gene Expression in Brain and Pituitary Gland

Abstract: The brain has been recognized as a prominent site of peptide biosynthesis for more than 30 years, and many neuropeptides are now known to be common to gut and brain. With these precedents in mind it is remarkable that adipose-derived peptides like leptin have attracted minimal attention as brain-derived putative neuromodulators of energy balance. This review outlines the evidence that several adipose-specific genes are also expressed in the central nervous system and pituitary gland. We, and others, confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 327 publications
(259 reference statements)
0
82
1
1
Order By: Relevance
“…This could reflect that the 2-wk training is insufficient to produce a substantial elevation of adiponectin in the circulation (12) or that exercise potentially facilitates the transport of adiponectin from the circulation into the brain. It is also possible that this increase was produced by adipose or nervous tissues inside the brain (33).…”
Section: Discussionmentioning
confidence: 99%
“…This could reflect that the 2-wk training is insufficient to produce a substantial elevation of adiponectin in the circulation (12) or that exercise potentially facilitates the transport of adiponectin from the circulation into the brain. It is also possible that this increase was produced by adipose or nervous tissues inside the brain (33).…”
Section: Discussionmentioning
confidence: 99%
“…This regulation is likely to be highly complex, involving the dopaminergic system, and psychosocial factors including stress [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in primary rat pituitary cells, GnRH treatment suppressed pituitary adiponectin expression (Kim et al 2013). AdipoRs have been identified in gonadotropin-producing cells in the pars distalis but not in the pars tuberalis in the human pituitary (Wilkinson et al 2007). To our knowledge, a sexual dimorphism has been described in the levels of circulating plasma adiponectin, with males having lower adiponectin levels than females (Arita et al 1999).…”
Section: Adiponectin and Resistin Expression And Action At Hypothalammentioning
confidence: 99%
“…Despite the conflicting evidence as to whether adiponectin can cross the blood-brain barrier, some studies have reported adiponectin and AdipoR expression in the brain and pituitary of various species, including humans, rats, pigs, rodents and chickens (Rodriguez-Pacheco et al 2007, Wilkinson et al 2007, suggesting that adiponectin may be a factor modulating the reproductive functions. AdipoRs have been identified in the hypothalamic GnRH neuron cells (GT1-7) and in human and rodent hypothalami, including in the paraventricular nucleus and in the periventricular areas.…”
Section: Adiponectin and Resistin Expression And Action At Hypothalammentioning
confidence: 99%